Changes of Proteases, Antiproteases, and Pathogens in Cystic Fibrosis Patients' Upper and Lower Airways after IV-Antibiotic Therapy. (21st June 2015) - Müller, Ulrike; Hentschel, Julia; Janhsen, Wibke K.; Hünniger, Kerstin; Hipler, Uta-Christina; Sonnemann, Jürgen; Pfister, Wolfgang; Böer, Klas; Lehmann, Thomas; Mainz, Jochen G.
Abstract : Background . In cystic fibrosis (CF) the upper (UAW) and lower airways (LAW) are reservoirs for pathogens like Pseudomonas aeruginosa . The consecutive hosts' release of proteolytic enzymes contributes to inflammation and progressive pulmonary destruction. Objectives were to assess dynamics of protease : antiprotease ratios and pathogens in CF-UAW and LAW sampled by nasal lavage (NL) and sputum before and after intravenous- (IV-) antibiotic therapy. Methods . From 19 IV-antibiotic courses of 17 CF patients NL (10 mL/nostril) and sputum were collected before and after treatment. Microbiological colonization and concentrations of NE/SLPI/CTSS (ELISA) and MMP-9/TIMP-1 (multiplex bead array) were determined. Additionally, changes of sinonasal symptoms were assessed (SNOT-20). Results . IV-antibiotic treatment had more pronounced effects on inflammatory markers in LAW, whereas trends to decrease were also found in UAW. Ratios of MMP-9/TIMP-1 were higher in sputum, and ratios of NE/SLPI were higher in NL. Remarkably, NE/SLPI ratio was 10-fold higher in NL compared to healthy controls. SNOT-20 scores decreased significantly during therapy( P = 0.001 ) . Conclusion . For the first time, changes in microbiological patterns in UAW and LAW after IV-antibiotic treatments were assessed, together with changes of protease/antiprotease imbalances. Delayed responses of proteases and antiproteases to IV-antibiotic therapy were found in UAW compared to LAW.